Bài 57 trang 218 SGK Đại số 10 Nâng cao

Bình chọn:
4 trên 4 phiếu

Chứng minh rằng:

Chứng minh rằng:

a) \(2\sin ({\pi  \over 4} + \alpha )\sin ({\pi  \over 4} - \alpha ) = \cos 2\alpha \)

b) \(sinα (1 + cos2α) = sin2α cosα\)

c) \({{1 + \sin 2\alpha  - \cos 2\alpha } \over {1 + \sin 2\alpha  + \cos 2\alpha }} = \tan \alpha \) (khi các biểu thức có nghĩa)

d) \(\tan \alpha  - {1 \over {\tan \alpha }} =  - {2 \over {\tan 2\alpha }}\) (khi các biểu thức có nghĩa)

Đáp án

a) Ta có:

\(2\sin ({\pi  \over 4} + \alpha ).sin({\pi  \over 4} - \alpha ) \)

\(= \cos 2\alpha  - \cos {\pi  \over 2} = \cos 2\alpha \)

b) Ta có:

\(\eqalign{
& sin\alpha \left( {1 + cos2\alpha } \right) \cr&= \sin \alpha (1 + 2{\cos ^2}\alpha - 1) \cr
& = 2\sin \alpha {\cos ^2}\alpha = \sin 2\alpha \cos \alpha \cr} \)

c)

\(\eqalign{
& {{1 + \sin 2\alpha - \cos 2\alpha } \over {1 + \sin 2\alpha + \cos 2\alpha }} = {{\sin 2\alpha (1 - \cos 2\alpha )} \over {\sin 2\alpha (1 + \cos 2\alpha )}} \cr
& = {{\sin 2\alpha + 2{{\sin }^2}\alpha } \over {\sin 2\alpha + 2{{\cos }^2}\alpha }} = {{2\sin \alpha (cos\alpha + sin\alpha )} \over {2\cos \alpha (cos\alpha + sin\alpha )}} \cr&= \tan \alpha \cr} \)

d)  

\(\tan \alpha  - {1 \over {\tan \alpha }} = 2.{{{{\tan }^2}\alpha  - 1} \over {2\tan \alpha }} =  - {2 \over {\tan 2\alpha }}\)

Loigiaihay.com

Các bài liên quan